Innovation in Focus: Do Two Famous Droids Signal the Future of Eye Care? - Lahey, Rhona; Wroten, Chris (Canadian Journal of Optometry, 2019)
Artifical intelligence has become commonplace in society, so that many things once considered revolutionary are no longer even considered AI. Examining some of AI's hisotrical milestones and understanding a few basic terms will allow us to better understand several current AI health care projects and their potential impact on eye care.